A case report of Pseudomonas citronellolis and Escherichia coli isolated from acute suppurative appendicitis: reveals the potential intestinal colonization and pathogenicity of Pseudomonas citronellolis - Lin, Yugui; Li, Yanfen; Lin, Chunxiu (Frontiers in Cellular and Infection Microbiology, 2024)
Human infections caused by Pseudomonas citronellolis, an environmental bacterium, are infrequent, with only two cases related to uncommon urinary tract infections and bacteremia reported in recent years. All these cases typically occurred in elderly patients with compromised or decreased immune function. Simultaneously, the epithelial barrier disruption induced by invasive biopsy procedures or gastrointestinal disorders such as gastroenteritis provided a pathway for Pseudomonas citronellolis to infiltrate the organism. In this study, we present the first report of a case where Pseudomonas citronellolis and Escherichia coli were isolated from the inflamed appendix of a patient without underlying conditions. Compared to the Escherichia coli, Pseudomonas citronellolis has never been isolated in patients with appendicitis. We identified the species using MALDI-TOF MS and genetic sequencing. Based on our findings, we highlight the perspective that Pseudomonas citronellolis can colonize the intestines of healthy individuals and may trigger infections like appendicitis.